D-Pinitol Remediates Heavy Metal Toxicity in Caenorhabditis elegans (Indian Journal of Nematology, 2024)
D-pinitol (DPI) is an alicyclic polyalcohol from the group ‘Cyclitols’ which possesses multifunctional properties. The present study delineates the effect of different doses of D-pinitol (DPI) (0.1. 0.01 and 0.001 mg/ml) on toxicity induced by four major environmental contaminants viz. cadmium, mercury, chromium and nickel in Caenorhabditis elegans. The maximum inhibitory effect was demonstrated by cadmium, mercury and chromium (10 and 100μM) affecting reproductive health and life span in C. elegans. Whereas, nickel was found to be least toxic in comparison to other three pollutants. Furthermore, DPI treatment prolonged lifespan in C. elegans. The 0.001 mg/ml dose of DPI was found to be most effective dose inducing tolerance against cadmium, mercury, nickeland chromium toxicity followed by other two doses viz 0.01mg/ml and 0.1mg/ml. DPI was able to alleviate heavy metal induced stressmediating improved survival in C. elegans. This bioactive molecule can contribute in designing remedies for heavy metal inducedtoxicity and disorders.